2013
DOI: 10.1016/j.neuron.2012.12.027
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomical Plasticity of Adult Brain Is Titrated by Nogo Receptor 1

Abstract: SUMMARY Experience rearranges anatomical connectivity in the brain, but such plasticity is suppressed in adulthood. We examined the turnover of dendritic spines and axonal varicosities in the somatosensory cortex of mice lacking Nogo Receptor 1 (NgR1). Through adolescence, the anatomy and plasticity of ngr1 null mice are indistinguishable from control, but suppression of turnover after age 26 days fails to occur in ngr1−/− mice. Adolescent anatomical plasticity can be restored to one-year old mice by condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
92
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 45 publications
9
92
3
Order By: Relevance
“…Similar to preceding publications [11], [20], [30], we observe that ngr1 −/− mice exhibit a mild deficit in performance. Despite this lower overall performance, ngr1 −/− mice improve over subsequent trials similar to WT mice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to preceding publications [11], [20], [30], we observe that ngr1 −/− mice exhibit a mild deficit in performance. Despite this lower overall performance, ngr1 −/− mice improve over subsequent trials similar to WT mice.…”
Section: Discussionsupporting
confidence: 91%
“…3G). A previous study reported that the 14-day stability of spines in ngr1 −/− mice was quadruple that of WT mice [11]. However, we observe that ngr1 −/− mice display basal spine formation, spine retraction, and new spine stability in barrel cortex that are indistinguishable from WT mice.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…These inhibitory ligands may function as "molecular brakes" by signaling through NgR1 to limit structural synaptic plasticity that could contribute to improving acuity after LTMD (Morishita and Hensch, 2008;Holtmaat and Svoboda, 2009). Consistent with this hypothesis, suppressing NgR1 expression in primary hippocampal neurons by RNA interference increases the formation of excitatory synapses in vitro (Wills et al, 2012), and NgR1 mutant mice have been reported to display elevated basal turnover of dendritic spines in visual cortex (Akbik et al, 2013). It would be interesting to examine whether the number of excitatory synapses made onto L2/3 PV interneurons is altered by NgR1 deletion or restoration of normal vision following LTMD may differentially affect structural synaptic plasticity in NgR1 mutant mice.…”
Section: Discussionmentioning
confidence: 86%
“…However, spine density is normal in both ngr1 Ϫ/Ϫ mice and transgenic mice overexpressing NgR1 (Lee et al, 2008;Karlén et al, 2009). Likewise, ngr1 Ϫ/Ϫ mice have been reported to display both dramatically elevated spine formation and new spine stability in vivo (Akbik et al, 2013). Yet we have performed similar, in some cases nearly identical, experiments with the same strain of ngr1 Ϫ/Ϫ mice, but we are unable to reproduce these findings.…”
Section: Discussionmentioning
confidence: 99%